Peptide Mediated Antimicrobial Dental Adhesive System - Xie, Sheng-Xue; Boone, Kyle; VanOosten, Sarah Kay; Yuca, Esra; Song, Linyong; Ge, Xueping; Ye, Qiang; Spencer, Paulette; Tamerler, Candan (MDPI, 2019)
The most common cause for dental composite failures is secondary caries due to invasive bacterial colonization of the adhesive/dentin (a/d) interface. Innate material weakness often lead to an insufficient seal between the adhesive and dentin. Consequently, bacterial by-products invade the porous a/d interface leading to material degradation and dental caries. Current approaches to achieve antibacterial properties in these materials continue to raise concerns regarding hypersensitivity and antibiotic resistance. Herein, we have developed a multi-faceted, bio-functionalized approach to overcome the vulnerability of such interfaces. An antimicrobial adhesive formulation was designed using a combination of antimicrobial peptide and a epsilon-polylysine resin system. Effector molecules boasting innate immunity are brought together with a biopolymer offering a two-fold biomimetic design approach. The selection of epsilon-polylysine was inspired due to its non-toxic nature and common use as food preservative. Biomolecular characterization and functional activity of our engineered dental adhesive formulation were assessed and the combinatorial formulation demonstrated significant antimicrobial activity against Streptococcus mutans. Our antimicrobial peptide-hydrophilic adhesive hybrid system design offers advanced, biofunctional properties at the critical a/d interface.
Keywords: antimicrobial peptide; polylysine; adhesive formulation; hybrid interface; dental composites; ENGINEERED CHIMERIC PEPTIDES; PROTEIN SECONDARY STRUCTURE; QUATERNARY AMMONIUM; PHASE-SEPARATION; BOND STRENGTH; TITANIUM; CHLORHEXIDINE; RAMAN; PREVENTION; INTERFACE; Chemistry; Engineering; Materials Science; Physics